Simultaneous injection effective mixing analysis system for the determination of direct bilirubin in urinary samples - Kraingkrai Ponhong (2018)
A novel simultaneous injection effective mixing analysis system (SIEMA) for determination of direct bilirubin in urine sample was developed. Bilirubin reacts with diazotized sulfanilic acid in the presence of n-octyl-β-d- thioglucoside (OTG) as a solubilizing agent to form OTG-azobilirubin. The flow and chemical variables were investigated. A linear calibration graph for direct bilirubin was obtained over the range of 0-1.0 mg L-1(r2= 0.994) with the limit of detection (3σ) of 4.7 μg L-1, and the relative standard deviation (RSD) being 1.9% (n = 11, 0.5 mg L-1of direct bilirubin). The results in healthy adult urine obtained by the proposed approach were found in good agreement with those obtained by the batch-wise diazo method. © 2011 Elsevier B.V. All rights reserved.